2015
DOI: 10.1038/nplants.2015.185
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of glyoxalase I in Brassica napus stigma leads to self-incompatibility response

Abstract: Self-incompatibility (rejection of 'self'-pollen) is a reproductive barrier that allows hermaphroditic flowering plants to prevent inbreeding, to promote outcrossing and hybrid vigour. The self-incompatibility response in Brassica involves allele-specific interaction between the pollen small cysteine-rich, secreted protein ligand (SCR/SP11) and the stigmatic S-receptor kinase (SRK), which leads to the activation of the E3 ubiquitin ligase ARC1 (Armadillo repeat-containing 1), resulting in proteasomal degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 23 publications
2
69
0
Order By: Relevance
“…Stigma-specific RNAi suppression of GLO1 in compatible B. napus Westar lines resulted in a significant reduction in pollen attachment and seed set, indicating the role of GLO1 as a compatibility factor to mediate successful pollination [60]. Interestingly, in the strong RNAi lines, during pod growth, we consistently observed development of a zone of tissue death, on the top half of the pod that radiated from the stigma (Figure 3A).…”
Section: Functional Roles Of Glyoxalases In Plants: From the Past mentioning
confidence: 89%
See 1 more Smart Citation
“…Stigma-specific RNAi suppression of GLO1 in compatible B. napus Westar lines resulted in a significant reduction in pollen attachment and seed set, indicating the role of GLO1 as a compatibility factor to mediate successful pollination [60]. Interestingly, in the strong RNAi lines, during pod growth, we consistently observed development of a zone of tissue death, on the top half of the pod that radiated from the stigma (Figure 3A).…”
Section: Functional Roles Of Glyoxalases In Plants: From the Past mentioning
confidence: 89%
“…Using a DIGE (difference gel electrophoresis)-based proteomics assay, we had previously identified glyoxalase I (GLO1) as one of the major candidates downregulated following SI response in Brassica napus [68,69]. Functional analysis of the role of GLO1 during pollination using isogenic Brassica napus lines (self-compatible Westar and the self-incompatible W1) revealed that GLO1 activity is essential for compatible pollination to occur [60]. Biochemical assays to measure GLO1 activity and levels revealed a significant increase in GLO1 activity and levels following compatible pollinations (CP) within 60 min and a significant reduction in GLO1 activity and levels within 60 min after SI pollinations.…”
Section: Functional Roles Of Glyoxalases In Plants: From the Past mentioning
confidence: 99%
“…In Arabidopsis , loss of the AtGLYI-2 gene, encoding a Zn 2+ -stimulated GLYI enzyme, has been shown to confer MG and NaCl sensitivity to the plants, with even lower doses of MG causing severe growth retardation in Arabidopsis [15]. Recently, the role of GLYI as a stigmatic compatibility factor has also been demonstrated in Brassica napus [95]. GLYI has been shown to be required for pollination to occur and is a target of the self-incompatibility system for preventing inbreeding or promoting hybrid vigor [95].…”
Section: Physiological Role Of Glyoxalases In Living Systemsmentioning
confidence: 99%
“…Recently, the role of GLYI as a stigmatic compatibility factor has also been demonstrated in Brassica napus [95]. GLYI has been shown to be required for pollination to occur and is a target of the self-incompatibility system for preventing inbreeding or promoting hybrid vigor [95]. Suppression of GLYI resulted in reduced compatibility, and its overexpression in self-incompatible B. napus stigmas led to a partial breakdown of the self-incompatibility response.…”
Section: Physiological Role Of Glyoxalases In Living Systemsmentioning
confidence: 99%
See 1 more Smart Citation